Design and engineer a domestic-use vertical farm for growing green vegetables and herbs - Chew, Sze Yen (Nanyang Technological University, 2024)
Singapore’s land constraints mean that there is very little land available for agricultural purposes and most of our produce is imported. Yet, there is a growing demand for freshly grown produce for culinary use, particularly for use at home in the face of rising food costs. This report describes the developmental process of a solution through vertical farming that allows home owners to establish a viable, sustainable source of fresh produce. A modular system was designed with a focus on functionality, sustainability and aesthetics. Field trips were undertaken to determine the most appropriate farming system and approach, and simulations were performed in order to choose the right material and optimize manufacturing efficacy. Finally, electronic components ensure that the system can function with minimal user input and provide a consistent optimized condition for plants to grow. Finally, a working prototype was developed from the above tests. This report also describes some future areas of work which would be required in order for the prototype to be manufactured on a large scale.